Meningkatkan Hasil Belajar Lari Sprint 60 Meter Melalui Metode Part Whole Part di SDN 002 Babulu - Agung Nurhadi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This research aims to improve learning outcomes for 60 meter sprint running using the Part Whole Part method for class IV students at SDN 002 Babulu, North Penajam Paser Regency. The form of research used is classroom action research. The subjects in this research were class IV students at SD Negeri 002 Babulu, North Penajam Paser Regency, totaling 27 students consisting of 12 boys and 15 girls. In the first cycle of students there were 15 students who completed the results or 44.4. %, while the number of students who had not yet completed was 15 or 55.6%, continuing to cycle II, there was an extraordinary increase in the complete category, with 27 students passing and 0 or none having completed. Based on the results of this research, it shows that learning using the part whole part method can improve learning outcomes for the 60 meter sprint in class IV students at SD Negeri 002 Babulu, North Penajam Paser Regency.